A resilience-enabling environment for farming systems: Patterns and principles - Erik Mathijs; Jo Bijttebier; Francesco Accatino; Peter H. Feindt; Camelia Gavrilescu; Gordana Manevska-Tasevska; Miranda P. M. Meuwissen; Franziska Ollendorf; Mariya Peneva; Carolina San Martín; Simone Severini; Alisa Spiegel; et al. (Resilient and sustainable farming systems in Europe: Exploring diversity and pathways, 2022)
This chapter aims to formulate principles and recommendations for an enabling environment that fosters resilience of farming systems. Principles have been derived from archetypical patterns identified in the various case studies on how actions in the enabling environment tend to constrain the resilience of farming systems.
Keywords: 330; farming system; resilience; enabling environment; systems archetypes